(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the unique features of literary text that distinguish it from other types of text, the essence of literary text analysis, its role and development in literary studies, and the necessity of studying it as a separate scientific field. The author thoroughly discusses the theoretical foundations of this art form based on theoretical and historical approaches to literary texts. The article also reviews historical sources related to the development of literary text analysis in Eastern and Western cultures and considers the methodology of literary text analysis.